2000
DOI: 10.1001/archpedi.154.5.435
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Early Detection of Human Immunodeficiency Virus Infection Among Adolescents

Abstract: While a significant and increasing number of adolescents are infected with the human immununodeficiency virus (HIV), few youth are identified as seropositive and even fewer are linked to medical care and social services. If more youth were identified, transmission to sexual partners and offspring would be reduced and individuals could benefit from treatment. Prior to initiating wide-scale early detection for HIV, we must (1) examine alternative strategies of conducting pretest and posttest counseling; (2) addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 51 publications
(51 reference statements)
0
51
0
Order By: Relevance
“…Other studies have found that approximately 80% of those infected are young MSM, and have not been informed of their diagnosis. 10,11 These data cause concern because people who have not received their diagnosis of HIV are responsible for transmission of about 50% of new cases. 12 In Colombia, the Pan American Health Organization 13 has called for broadening the scope of, and guaranteeing access to HIV testing.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have found that approximately 80% of those infected are young MSM, and have not been informed of their diagnosis. 10,11 These data cause concern because people who have not received their diagnosis of HIV are responsible for transmission of about 50% of new cases. 12 In Colombia, the Pan American Health Organization 13 has called for broadening the scope of, and guaranteeing access to HIV testing.…”
Section: Introductionmentioning
confidence: 99%
“…Even among individuals who suspect they may have been exposed to HIV, testing is often delayed, sometimes for longer than a year (59,60 (74). Data from adolescent medicine clinics (75) suggests that only about 11% of identified youth living with HIV are linked to care (76). Although linking seropositive persons to care is an important goal in itself, increasing the proportion of infected individuals who are referred to and followup in care will also help to decrease rates of HIV transmission.…”
Section: Shifting Context Of Hiv Testingmentioning
confidence: 99%
“…Mainstreaming of HIV testing refers to offering HIV testing as a routine procedure in primary health care with an informed right of refusal (i.e., voluntary opt-out), rather than relying on client requests for testing (i.e., voluntary opt-in) (76,125). In routine testing, the burden is shifted from those who would want to take an HIV test to those who want to refuse testing.…”
Section: Mainstream Hiv Testing As Routine Clinical Carementioning
confidence: 99%
See 2 more Smart Citations